Synthesis of Novel Nicotinic Ligands with Multimodal Action: Targeting Acetylcholine α4β2 Dopamine and Serotonin Transporters - Reyes-Parada, M (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
Nicotinic acetylcholine receptors (nAChRs), serotonin transporters (SERT) and dopamine transporters (DAT) represent targets for the development of novel nicotinic derivatives acting as multiligands associated with different health conditions, such as depressive, anxiety and addiction disorders. In the present work, a series of functionalized esters structurally related to acetylcholine and nicotine were synthesized and pharmacologically assayed with respect to these targets. The synthesized compounds were studied in radioligand binding assays at α4β2 nAChR, h-SERT and h-DAT. SERT experiments showed not radioligand [3H]-paroxetine displacement, but rather an increase in the radioligand binding percentage at the central binding site was observed. Compound 20 showed Ki values of 1.008 ± 0.230 µM for h-DAT and 0.031 ± 0.006 µM for α4β2 nAChR, and [3H]-paroxetine binding of 191.50% in h-SERT displacement studies, being the only compound displaying triple affinity. Compound 21 displayed Ki values of 0.113 ± 0.037 µM for α4β2 nAChR and 0.075 ± 0.009 µM for h-DAT acting as a dual ligand. Molecular docking studies on homology models of α4β2 nAChR, h-DAT and h-SERT suggested potential interactions among the compounds and agonist binding site at the α4/β2 subunit interfaces of α4β2 nAChR, central binding site of h-DAT and allosteric modulator effect in h-SERT. © 2019 by the authors.